A proposed method for outlining occluded intracranial artery using 3D T2-weighted sampling perfection with application optimized contrasts using different flip angle evolution (SPACE). (March 2021) - Ozaki, Saya; Okamoto, Shigetaka; Shinohara, Naoki
High-resolution vessel wall imaging techniques have been developed for clinical use in various types of intracranial artery disease. Numerous studies have described techniques for evaluating remodeling patterns and plaque character, but few have reported a method for outlining obstructed vessels in intracranial artery occlusion. The course of the vessel affects the success of recanalization and can cause complications in mechanical thrombectomy for acute ischemic stroke. We propose imaging with 3D T2-weighted sampling perfection with application optimized contrasts using different flip angle evolution (SPACE) as a useful tool for describing the course of an occluded artery in ischemic stroke due to intracranial artery occlusion.